Modal Saturation Detector for Digital Differential Protection - Hosemann, Gerhard; Steigerwald, Hubert Maria (IEEE Transactions on Power Delivery, 1993)
A new digital method for the rapid and reliable detection of current transformer saturation for single and multiple pole short circuits is described. The function principle is independent of the number of phases envolved ir the short-circuit and independent of the magnetic properties of the current transformers including remanence. In order to achieve this, the secondary currents of the three phases are transformed into space phasors with a blocked backward rotating component. In the unsaturated state their trajectories are circles. The deviation from this characteristic form and hence the inception of current transformer saturation can be detected in less than 3 milliseconds. One result of quick detection of the current transformer saturation is that the differential protection can be adjusted to higher sensitivity than in known protection devices. This guarantees reliable operation even in case of short circuits with weak short-circuit currents. The new modal saturation detector is equally suited for the differential protection of lines as well as busbars and other circuit arrangements. © 1992 IEEE
UnivIS-Import:2017-12-18:Pub.1993.tech.IE.leen.modals